Pemanfaatan Teknologi Pendidikan dalam Meningkatkan Karakter Anak Bangsa di Era Digital - Hafidh Satria; Rafka Bulan Nafisa; Silvi Vadila Putri; Gusmaneli Gusmaneli (IDRIS Darulfunun Institute, 2023)
Education plays a key role in shaping the character of the nation's children. In today's digital era, technology has great potential to improve education and develop children's character. This research aims to explain how the utilisation of technology in education can be an effective means to improve the character of the nation's children. The research involves a literature analysis to explore the role of technology in the context of character education. The findings show that the integration of technology into the curriculum can facilitate more interactive learning, present moral challenges, and increase student engagement. In addition, the use of technology can help develop critical skills, cooperation and problem-solving, all of which are important aspects of character. However, this research also underlines the need for a balanced approach. While technology provides benefits, character education still requires a holistic approach involving social interaction, cultural values and balanced personality development. Therefore, this research provides insights into how technology can be positively integrated into the education curriculum to improve the character of the nation's children. The results of this research are expected to provide practical guidance for educators, policymakers and curriculum makers in developing educational strategies that focus on the character of the nation's children through the utilisation of technology. Thus, it is expected to realise a young generation that is not only technologically competent but also has a strong character that can face global challenges with integrity and leadership.